Profil Hitung Jumlah dan Jenis Leukosit Pada Anak Terinfeksi Kecacingan Kota Samarinda - Ade Tasya Halim; Sresta Azahra (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Helminthic infections are caused by helminth parasites. Helminthic worms are health problems that affect the defenses of the human immune system such as leukocytes. Children infected with helminthic worms are characterized by an increase in the number of eosinophils due to an immune response to helminthic infection. The purpose of knowing the profile of counting the number and type of leukocytes in children infected with worms. Type of descriptive research with cross sectional design. The total population is 187 children with 9 children infected with worms in Samarinda City. This study was carried out by fecal examination (microscopic), leukocyte count examination (counting chamber) and leukocyte count (differential count). Analysis of data in univariate form. The results of the study found 9 children (5%) infected with worms, 5 children (3%) male aged 6-12 years and 4 children (2%) female aged 8-10 years. Types of worm eggs obtained 5 children (56%) Ascaris lumbricoides, 2 children (22%) Trichuris trichiura and 2 children (22%) Hymenolepis nana. The number of leukocytes in infected children is within normal limits (4,500-13,500 μL). The type of abnormal leukocytes was obtained by 4 children (45%) who had elevated eosinophils. Conclusion The number of leukocytes in infected children is within normal limits and the type of leukocytes that have increased in the number of eosinophils (45%) indicates an immune response to helminthic infection.